Time course of cisplatin-induced nephrotoxicity and hepatotoxicity - Pezeshki, Zahra (J Nephropathol, 2017)
BACKGROUND: One of the main therapeutic limitations of cisplatin (CP) is nephrotoxicity which is time-dependent. OBJECTIVES: The purpose of this study was to determine the optimal timing for initiation of CP toxicity. MATERIALS AND METHODS: Sixty male and female Wistar rats were randomly divided into five groups. All the animals in groups 2-5 received single dose of CP (10 mg/kg; i.p.), and were evaluated 25, 50, 75, and 100 hours after CP administration. Group 1 as an untreated group did not receive any agent and was considered as time zero. RESULTS: The data indicated time-dependent progression of kidney and hepatic toxicity due to CP administration. Histological examination showed increase in kidney tissue damage score (KTDS) at hour 25, which peaked 75-100 hours after CP administration. Significant body weight loss and reduction of alkaline phosphatase (ALP) 50 hours after CP injection were observed. Blood urea nitrogen (BUN), creatinine (Cr), and serum nitrite increased significantly 75 hours after CP injection. Also, enhancement of kidney and testis weights, and alkaline aspartate aminotransferase (AST) level; and reduction of alanine aminotransferase (ALT) level and uterus weight occurred significantly 100 hours after the injection, while kidney malondialdehyde level enhanced significantly 75 hours after CP administration. CONCLUSIONS: These findings suggest that the CP-induced nephrotoxicity started to develop almost 3 days after administration of the drug in rats. CP surprisingly reduced the serum levels ALP and ALT while AST increased 100 hours after CP injection. CP-induced nephrotoxicity and hepatotoxicity are time-dependent, and the related biomarkers may alter by different trends.